Stress Testing of Banking Systems: an examination against the Shocks of Macroeconomic Variables - Askari, Kamiar (2021)
In the past years, overdue due receivables of the banks have increased in an unprecedented way compared to all the facilities granted in Iran’s banking network, showing the not very acceptable quality of bank assets that decrease the bank credit and make them financially unstable. The macroeconomic variables in this article are as follow: GDP growth rate, economic growth, exchange rate, inflation rate, unemployment rate, government debt. The decrease in this amount of arrears shows the ability of banks to maintain their resources. At this research, after identifying the macroeconomic variables affecting the default of banks using the stress test and applying one standard deviation with the help of the historical scenario, the study examined the banks’ resilience to the shocks of these variables from 2006 to 2019. The results indicated that the shock of the economic growth rate had the greatest effect. In other words, the decrease in the economic growth rate had the greatest effect on the increase of borrowers’ default rates. In addition to this, shocks of economic growth and government debt have highly effect on the borrowers’ default rates and inflation rate, unemployment rate, GDP growth rate and exchange rate have a significant impact upon borrowers’ default rates.